Reduction in contraceptive use during the COVID-19 pandemic among women in an indigenous Mexican community: a retrospective crossover study - Castro-Porras, Lilia V.; Aguilar-Rodríguez, María Alejandra; Rojas-Russell, Mario E.; Salinas-Iracheta, Bertha A. (Frontiers in Public Health, 2023)
Background. Being indigenous, being a woman, and living in poverty are social determinants that contribute to reduced access to healthcare, including reproductive health services. The COVID-19 pandemic might have exacerbated this lag. Objective. This study explored how the COVID-19 pandemic affected the contraceptive use of a group of indigenous Mexican women and adolescents in their community. Methods. Between June and December of 2021, 158 indigenous Mexican women who had experienced recurrent pregnancies were interviewed at two health centers in San Cristóbal de las Casas, Chiapas. Participants were either pregnant when they completed the questionnaire or had been pregnant during the COVID-19 pandemic. Women were asked about their contraceptive practices before and during the pandemic. The change in contraceptive practice was estimated using a logistic model. Results. The COVID-19 pandemic reduced contraceptive use by 50%. Among women who wanted contraception, 58% did not receive it. During the pandemic, 77% of previous contraceptive users reported difficulty obtaining contraception, and only 23% sought family planning assistance. Conclusion. During the COVID-19pandemic, indigenous women in the studied community used fewer contraceptive methods and did not use intrauterine devices. Additionally, there was a decline in the percentage of women using contraceptives.These results highlight the impact on indigenous populations and the difficulties they could face in accessing reproductive health services during health emergencies.